KEMAMPUAN MENULIS TAKARIR BERBASIS KARYA SASTRA DI MEDIA SOSIAL - Hidayat, Taufik; Wikanengsih, Wikanengsih; Yani, Aurelia Sakti (IKIP Siliwangi, 2020)
Many things will be affected by unstable emotions, including gestures to different ways of communicating. Words are one of the manifestations that a person can choose when their emotions are unstable, some express them directly and some are indirect in other words, preferring to put all their feelings into writing. This research is based on looking at the development of a person's writing in writing captions on social media, writing that definitely represents the feelings that the writer is experiencing. This study aims to describe the ability to write captions based on literary works on social media among students. This research method uses a qualitative descriptive method, using an observation sheet that discusses the ability to write captions based on literary works on social media. The sample of this study involved 15 students of the sixth semester of the Indonesian Language and Literature Education IKIP Siliwangi taken from class A2-2016 representing each level of writing ability. The results of this study indicate the ability to write literary based captions on social media in which there are differences between students who like and dislike literary works. This is evidenced by the data obtained that those who have the ability to write and fall into the good category in writing subtitles are 8 people, 4 are not good and 3 are not good.